CHRISTIANITY AND POWER: AN ANCIENT MISCONCEPTION (Ad Aeternum, 2020)
Abstract The history of civilizations is largely tied to the religious domain in its most diverse forms. From the most explicit to the most subtle, from the days of Constantine to the present day, from the West to the East and involving practically all expressions and branches of the Christian faith. This domain is verified in terms of content as well as form. This thirst for power in both appearance and substance clearly shows how the essence of the Gospel was not properly assimilated by Christians throughout History, or at least was not more important than acquiring power in ancient times, whether through self-defense or as Camões would put it: “the vain glory of ruling.”Keywords: Christianity, power, misconception ResumoA história dos povos é em grande parte a história do domínio religioso nas suas mais diversas formas, desde as mais explícitas às subtis, desde os dias de Constantino até hoje, do Ocidente ao Oriente e envolvendo praticamente todas as expressões e ramos da fé cristã. Domínio esse que se verifica tanto no conteúdo como na format. Esta ânsia pelo poder, tanto na aparência como na substância, mostra bem como a essência do Evangelho não foi assimilada pelos cristãos ao longo da História, ou pelo menos não terá sido mais determinante do que a oportunidade de ocupar o poder secular, seja com intenções de auto-defesa, seja tendo como motivação aquilo que Camões chamava a “vã glória de mandar”.Palavras-chave: Cristianismo, poder, equívoco